Locus of Control Mediates The Impact of Financial Knowledge, Attitudes, and Experience on Financial Behavior - Santoso, Rahmat Agus; Vilantika, Elok; Soelistya, Djoko; Liu, Yaoping (Jurnal Manajemen Bisnis, 2024)
Research aims: This study aims to examine the effect of financial knowledge, attitudes, and experience on financial behavior, with locus of control serving as a mediating factor.Design/Methodology/Approach: This study employs a deductive research design with a causal-associative approach, targeting traditional market traders in the Gresik Regency area. A total of 100 respondents were sampled. The main data were collected through a questionnaire and analyzed using Partial Least Squares (PLS).Research findings: The study findings reveal that financial knowledge, attitudes, and experience positively influence locus of control. However, financial knowledge has a negative effect on financial behavior, while financial attitudes, experience, and locus of control have a positive effect. Notably, locus of control successfully mediates the positive relationship between financial knowledge, attitudes, experience, and financial behavior.Theoretical Contribution/Originality: This research uniquely expands the financial literacy model by incorporating the variable of financial experience. Practitioners/Policy Implications: The study findings are expected to serve as a reference model for the development and mentorship of small and medium enterprises in the Gresik district. Practitioners/Policy Implications: The findings are anticipated to serve as a reference model for the development and mentorship of Small and Medium Enterprises in the Gresik district.